2011
DOI: 10.1097/gme.0b013e3181fca9c4
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional and 10-year prospective study of postmenopausal estrogen therapy and blood pressure, renal function, and albuminuria

Abstract: Objective-Blood pressure, urine albumin-to-creatinine ratio, and estimated glomerular filtration rate (GFR), are highly correlated conditions. The longitudinal effect of exposure to postmenopausal estrogen therapy on these traits studied together has not been reported.Methods-A cross-sectional study of 1044 older postmenopausal community-dwelling women from the Rancho Bernardo Study (1992)(1993)(1994)(1995)(1996); 443 were re-evaluated ~10 years later (2002)(2003)(2004)(2005). We determined the cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 51 publications
5
33
0
2
Order By: Relevance
“…These results confirm differential pathogenesis of hypertension and its end-organ diseases in premenopausal and post menopausal states, as well as corroborate the role of ovarian hormones in postmenopausal hypertension–protective role(s) for blood pressure and for hypertensive renal disease. These observations are concordant with the studies reporting that estrogen/progestin replacement therapy improved renal function [8][10].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results confirm differential pathogenesis of hypertension and its end-organ diseases in premenopausal and post menopausal states, as well as corroborate the role of ovarian hormones in postmenopausal hypertension–protective role(s) for blood pressure and for hypertensive renal disease. These observations are concordant with the studies reporting that estrogen/progestin replacement therapy improved renal function [8][10].…”
Section: Discussionsupporting
confidence: 91%
“…In studies using ovariectomized Dahl-S rats as an animal model of surgically-induced postmenopausal salt-sensitive hypertension, 17β-estradiol attenuated age-related renal dysfunction [19], [20]. However, studies of hormone replacement therapy in aging women are controversial, with some studies showing improvement [8][10] and others showing loss of kidney function [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen supplementation also downregulated the AT 1 -receptor expression, linking augmented oxidative stress and the renin-angiotensin system to prolonged estrogen deprivation, but not necessarily to aging per se. In the recently published Rancho Bernardo Study, a 10-yr follow-up showed that, in postmenopausal women, estrogen use improved blood pressure and decreased urine albumin-to-creatinine ratio, without affecting in glomerular filtration rate (13). These observations suggest that continuous estrogen use attenuates albuminuria, which may be mediated by improved blood pressure control or possibly by decreased renal fibrosis, as observed in the present study.…”
Section: E984supporting
confidence: 67%
“…Results include the finding of the Women's Health Initiative (WHI) trial that hormone replacement with conjugated equine oestrogens (CEEs) results in a small increase in BP [33]. However, other studies have shown that CEEs result in a lower BP after 10 years of treatment [34]. It has been suggested that the method of HRT delivery influences CEEs' effects on BP.…”
Section: Sex Ovarian Hormones and Sympathetic Outflowmentioning
confidence: 96%